2011
DOI: 10.3171/2011.3.spine10832
|View full text |Cite
|
Sign up to set email alerts
|

Posterior epidural migration of a lumbar disc fragment: a series of 6 cases

Abstract: Object The migration of a lumbar intervertebral disc fragment to the posterior epidural space is a rare complication of lumbar disc herniation (LDH), mostly diagnosed intraoperatively. The authors describe a series of 6 patients with a posterior epidural migration of a lumbar intervertebral disc fragment (PEMLIF) and provide a systematic review of the literature. Methods The authors undertook a retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
44
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 37 publications
3
44
0
5
Order By: Relevance
“…PEMLIF as quoted in the literature is very rare. A recent review of literature by Akhaddar et al found that the total number of cases was only about 41 (10). This generally occurs in the setting of a degenerating spine pathology and patients usually give a previous history of backache like our second patient.…”
Section: Discussionmentioning
confidence: 98%
“…PEMLIF as quoted in the literature is very rare. A recent review of literature by Akhaddar et al found that the total number of cases was only about 41 (10). This generally occurs in the setting of a degenerating spine pathology and patients usually give a previous history of backache like our second patient.…”
Section: Discussionmentioning
confidence: 98%
“…In PEM of the lumbar disc, men outnumber the female with the ratio of 4 to1 and the patients of middle age are mostly affected 1,5,8,[10][11][12] .…”
Section: Discussionmentioning
confidence: 99%
“…Decision for urgent surgery should be the first step toward the elimination of pain and averting neurological deficit, particularly in the subjects with cauda equina syndrome. Removal of the sequestrated disc fragment can be achieved through hemilaminectomy 1,5,6 . Hopefully, the outcome is good in majority of the patients suffering from this pathology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations